Biocontrol of fungi isolated from sour rot infected table grapes by Saccharomyces and other yeast species - Nally, María Cristina; Pesce, Virginia Mercedes; Maturano, Yolanda Paola; Toro, María Eugenia; Combina, Mariana; Castellanos de Figueroa, Lucía Inés; Vazquez, Fabio (2017)
Sour rot is an important disease of grapes caused by an etiologic complex of microorganisms in which filamentous fungi play a key role. Yeasts are used for biocontrol of pathogenic filamentous fungi on fruits. The major objective of this study was to assess in vivo on detached berries the effect of viticultural yeasts on phytopathogenic fungi involved in grape sour rot. Yeasts that were found to be effective in vivo againstthe fungi were assayed for their possible pathogenicity in humans: growth at 42 ◦C, pseudohyphal formation, adhesion, and phospholipase and protease activity.Atotal of 234 yeasts belonging to 14 genera were assayed against the following pathogens: Aspergillus caelatus, Aspergillus carbonarius, Aspergillus terreus, Aspergillus versicolor, Fusarium oxysporum, Penicillium comune, Rhizopus stolonifer and Ulocladium sp. Forty-three (16 Saccharomyces and 27 non-Saccharomyces) showed antagonistic properties against some of the fungi assayed in grapes at 25 ◦C. Yeast isolates determined as biocontrol agents under in vivo conditions were isolated from fermenting musts (35), viticultural soils (6) and grape berries (2). Twenty biocontrol agents did not show phenotypical characteristics associated with pathogenicity in humans